Horti-Poultry model – A novel way for raising farmer’s income - Reshi, P A; Khan, A A; Bhat, J A; Bhadauria, Pragya (Indian Farming, 2020)
In the temperate climatic conditions of Kashmir Valley the model as was expected did well while establishing at the KVK level and has attracted scores of orchardists toadopt the model. The model being farmer friendly easy and economical to adopt is being spread on pilot basis in district Ganderbal of the J&K state. The integration of horticulture with poultry has given a new direction to the policy makers assigned to look for the ways and means of enhancing the farmers’ income. The model though in its initial stage and still under exhaustive trial at the KVK-Ganderbal has till given desired results in terms of weed control, supplementary income generation from KVK apple orchard, revolving fund generation, and other benefits. The model needs to be spread to the knock and corner of the country orchards through KVKs.